Anthropometrical, physiological, strength and other determinants of rowing performance - review of correlation-predictive analyses - Hellebrand, J. (Charles University, Faculty of Physical Education and Sport, 2023)
Objectives: To conduct a systematic literature review to search for a best single Performance variable(s) (a measure of performance) that is(are) associated with rowing performance.